2018
DOI: 10.1186/s12886-018-0915-y
|View full text |Cite
|
Sign up to set email alerts
|

A huge lacrimal gland ductule dacryolith with a hairy nucleus: a case report

Abstract: BackgroundDacryoliths in lacrimal gland ductule are a rare condition and an unusual cause of conjunctivitis. Here we report a case with a large lacrimal gland ductule stone with an unique hairy nucleus.Case presentationA 38-year-old female presented with a red left eye for one month. Physical examination revealed an inflammatory granuloma in the lateral canthus and a fistula with purulent secretion. Antibiotics did not ameliorate the symptoms. After we incised the fistula, a huge dacryolith (10 mm × 5 mm × 3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…There were many white deposits on the eyelashes. Dacryoliths with hair nuclei have been found and reported not only in the lacrimal sac but also in lacrimal gland ductules [12, 13]. Mano reported that the core proteins of dacryoliths can be characterized by immune and inflammatory responses, as confirmed by the top 20 abundant proteins [14].…”
Section: Discussionmentioning
confidence: 99%
“…There were many white deposits on the eyelashes. Dacryoliths with hair nuclei have been found and reported not only in the lacrimal sac but also in lacrimal gland ductules [12, 13]. Mano reported that the core proteins of dacryoliths can be characterized by immune and inflammatory responses, as confirmed by the top 20 abundant proteins [14].…”
Section: Discussionmentioning
confidence: 99%
“…Possible etiologies include stone formation around eyelashes and animal hair (particularly relevant for those working as rabbit raisers), and perhaps related to dacryoadenitis, which itself may be caused by infection. 7,11 The most recent case report by Othman et al from Japan in 2019, in this journal, discussed a lacrimal gland stone related to recurrent acute dacryoadenitis. Othman et al questioned whether the stone resulted from the dacryoadenitis, or whether the stone may have been the original cause of the dacryoadenitis.…”
Section: Etiologymentioning
confidence: 98%